Propagation characteristics of a high-power broadband laser beam passing through a nonlinear optical medium with defects - Xueqiong Chen; Xiaoyan Li; Ziyang Chen; Jixiong Pu; Guowen Zhang; Jianqiang Zhu (High Power Laser Science and Engineering, 2013)
The intensity distributions of a high-power broadband laser beam passing through a nonlinear optical medium with defects and then propagating in free space are investigated based on the general nonlinear Schrödinger equation and the split-step Fourier numerical method. The influences of the bandwidth of the laser beam, the thickness of the medium, and the defects on the light intensity distribution are revealed. We find that the nonlinear optical effect can be suppressed and that the uniformity of the beam can be improved for a high-power broadband laser beam with appropriate wide bandwidth. It is also found that, under the same incident light intensity, a thicker medium will lead to a stronger self-focusing intensity, and that the influence of defects in the optical elements on the intensity is stronger for a narrowband beam than for a broadband beam.